Ergonomic Work Facility Design for Appearance & Packing Line H3CR Operators at PT Omron Indonesia - Shelvi barqi laily shelvi (Batrisya Education, 2025)
PT Omron Manufacturing of Indonesia, an electronics sector company established on February 13, 1933, faces issues in its production department. Operator complaints due to poorly adjusted ergonomic work facilities hinder their ability to meet production targets. Using the Nordic Body Map method, the author investigated muscle complaints to identify the most affected muscles, which will guide the redesign of work facilities. Additionally, the REBA method was employed to assess the urgency of this redesign, incorporating anthropometric and user-centered design (UCD) methods to better tailor the facilities to user needs.